The effectiveness of child support grants in South Africa: A case study of Caledon district, Western Cape - Volmink, Mark Fritzgerald (University of Western Cape, 2020)
Magister Artium (Development Studies) - MA(DVS) === This research study addresses the effectiveness of child support grants in South Africa. It specifically asks the questions, what do social policy makers in South Africa want to achieve with the Child Support Grant (CSG) and are they achieving it? If not, how can policy makers ensure that social grants achieve the desired impact? The researcher will establish the effectiveness of the current CSG and how the CSG programme design and implementation might be improved for the CSG system to have its desired effect for children and at the family level.